Carbon stakeholder collaboration’s influence on the carbon accounting implementation of organizations in Malaysia - Kasbun, Nur Fatin; Ong, Tze San (Human Resource Management Academic Research Society, 2021)
Reduction of corporations’ direct or indirect carbon emissions is one of the most important yet complicated challenges facing by the society in the effort for climate change mitigation. It is also empirically proven that the industry and the industrial have been acknowledged as the major causes and contributors to carbon dioxide (CO2) emissions. Business corporations contribute to the success of converting natural resources into wealth, which have directly created today‘s sophisticated social world but unfortunately, at the same time, deteriorating the environment. The economic production forms unfortunately will continue to contribute to pollution. Consequently, in order to achieve sustainability, corporation specifically corporate accounting should not only focus on financial profitability but must take action to counter the effects of their greenhouse gases emissions especially carbon dioxide, the cause of climate change for the betterment of the environment. One of the ways is to collaborate with stakeholders in the effort of carbon emissions mitigation because the hazardous impacts of climate change are not only affecting the environment but also the economy.